Structure, Distribution and Formation of Submarine Permafrost (Osobennosti Stroeniia, Rasprostraneniia i Formirovaniia Subakval'noi Kriogenno i Tolshchi) - Zhigarev,L. A.; Piakht,I. R. (1976)
This research conducted in the eastern part of the Laptev Sea has once again confirmed the extremely complex nature of the subaquatic cryozenic stratum, which is expressed by the instability and dynamicity of this layer. The thermal state and structure of submarine permafrost, the thermodynamic aspects of the conditions for the formation, preservation and destruction of cryozenic formations on the shelf are discussed. (Author) Draft trans. of mono. Problems of Cryolithology (USSR) 1974 p115-124.